2023
DOI: 10.1371/journal.pone.0284009
|View full text |Cite
|
Sign up to set email alerts
|

Conjoint application of nano-urea with conventional fertilizers: An energy efficient and environmentally robust approach for sustainable crop production

Abstract: One of the biggest challenges to be addressed in world agriculture is low nitrogen (N) use efficiency (<40%). To address this issue, researchers have repeatedly underlined the need for greater emphasis on the development and promotion of energy efficient, and environmentally sound novel fertilizers, in addition to improved agronomic management to augment nutrient use efficiency for restoring soil fertility and increasing farm profit. Hence, a fixed plot field experiment was conducted to assess the economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In our study, we found that there are some effects of nano-urea on the growth and yield of wheat but cannot replace a bag of urea (45 kg urea or 20.7 kg of N) as claimed by product manufacturers. However, a recent research has supported two foliar sprays of nano-urea reduced the nitrogen load by 25% without negatively impacting crop yield of wheat, maize, mustard and pearl millet 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that there are some effects of nano-urea on the growth and yield of wheat but cannot replace a bag of urea (45 kg urea or 20.7 kg of N) as claimed by product manufacturers. However, a recent research has supported two foliar sprays of nano-urea reduced the nitrogen load by 25% without negatively impacting crop yield of wheat, maize, mustard and pearl millet 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Nano urea, being in nanoparticle form, likely provides a more controlled and sustained release of nitrogen, ensuring a consistent nutrient supply during critical growth stages. The higher yield in nano urea may be linked to improved photosynthetic efficiency (Upadhyay et al, 2023). Nano urea, as previously mentioned, likely contributes to increased interception of sunlight for photosynthesis due to sustained nitrogen availability (Astaneh et al, 2021).…”
Section: Measurement Of Yieldsmentioning
confidence: 91%
“…This increased translocation efficiency is associated with the smaller particle size of nano urea, allowing for better mobility within the plant's vascular system. Furthermore, the application of nano urea contributed to an elevated and sustained nitrogen supply during critical growth stages (Upadhyay et al, 2023). This sustained nitrogen availability facilitated an extended period of enhanced photosynthetic activity.…”
Section: Yield Attributing Parametersmentioning
confidence: 99%
“…This not only diminishes the requirement for nitrogen fertilizers and amplifies nitrogen utilization by plants but also curtails the adverse environmental impact, concurrently safeguarding agricultural yields [ 53 ]. In comparison to traditional nitrogen fertilizers, nano-nitrogen fertilizers exhibit notable advantages in enhancing crop yield and quality [ 54 ]. The precision of the release mechanism in nano-nitrogen fertilizers results in a more consistent and even supply of nitrogen, contributing to the maintenance of stable nitrogen levels in crops throughout the growth cycle.…”
Section: Nano-fertilizers In Farmingmentioning
confidence: 99%